Discrete modeling of ionic space charge zones in solids. Issue 19 (6th May 2022) - Xiao, Chuanlian; Chen, Chia-Chin; Maier, Joachim
Abstract : Discretization allows not only for a realistic treatment of space charge layers in solids but also for a straightforward incorporation of non-idealities. Abstract : The discrete model of space charge zones in solids reveals and remedies a variety of problems with the classic continuous Gouy–Chapman solution that occur for pronounced space charge potentials. Besides inherent problems of internal consistency, it is essentially the extremely steep profile close to the interface which makes this continuum approach questionable. Not only is quasi-1D discrete modeling a sensible approach for large space charge effects, it can also favorably be combined with the continuum description. A particularly useful application is the explicit implementation of crystallographic details and non-idealities close to the interface. This enables us to consider elastic, structural or saturation effects as well as permittivity variations in a simple but realistic way. We address details of the charge carrier profiles, but also overall properties such as space charge capacitance and space charge resistance. In the latter case the difference in the total charge (at identical concentration) is of importance, in the first case it is the inherent difference in the centroid of charge (at identical total charge) that is remarkable. The model is equally applicable for ionic charge carriers and small polarons.